2012
DOI: 10.1111/j.1742-7843.2012.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Oximes on Rat and Human Cholinesterases Inhibited by Methamidophos: A Comparative In Vitro and In Silico Study

Abstract: Methamidophos is one of the most toxic organophosphorus (OP) compounds. It acts via phosphorylation of a serine residue in the active site of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), leading to enzyme inactivation. Different oximes have been developed to reverse this inhibition. Thus, our work aimed to test the protective or reactivation capability of pralidoxime and obidoxime, as well as two new oximes synthesised in our laboratory, on human and rat cholinesterases inhibited by methamidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
12
2
Order By: Relevance
“…In vitro studies revealed that PHBO is an oxime with antioxidant and AChE reactivator potential in human blood. 11,28,46,47 However, in the present study, PHBO did not reactivate the AChE inhibited by malathion in A salina. Therefore, it is possible to assume that PHBO protected A salina from the death induced by malathion due to its antioxidant effect; nevertheless, further research is needed to validate this hypothesis.…”
Section: Discussioncontrasting
confidence: 79%
“…In vitro studies revealed that PHBO is an oxime with antioxidant and AChE reactivator potential in human blood. 11,28,46,47 However, in the present study, PHBO did not reactivate the AChE inhibited by malathion in A salina. Therefore, it is possible to assume that PHBO protected A salina from the death induced by malathion due to its antioxidant effect; nevertheless, further research is needed to validate this hypothesis.…”
Section: Discussioncontrasting
confidence: 79%
“…Besides being one of the metabolic products of acephate, MT is a systemic insecticide and acaricide. It is still used in developing countries, on some crops such as wheat, soybeans, potatoes, citrus fruits, cotton, and maize (Maroni et al, ; Araoud et al, ; Lugokenski et al, ; Uriostegui‐Acosta et al, ). World Health Organization (WHO) classified the technical product as Class 1B “Highly Hazardous,” and an Acceptable Daily Intake (ADI) of 0.004 mg/kg body weight was established by the Joint Meeting on Pesticide Residues (Maroni et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of post‐exposure treatment of acute poisonings with highly toxic organophosphorus compounds, especially soman, are well recognized . In situations allowing the administration of prophylactic agents, better therapeutic effects can be achieved by pre‐treatment with reversible AChE inhibitors .…”
Section: Discussionmentioning
confidence: 99%
“…soman, are well recognized [3][4][5][6][19][20][21][22]. In situations allowing the administration of prophylactic agents, better therapeutic effects can be achieved by pre-treatment with reversible AChE inhibitors [12,23].…”
Section: Discussionmentioning
confidence: 99%